Evaluasi Biaya Keluaran di Kantor Pelayanan Perbendaharaan Negara Tanjungpinang Tahun 2019-2021 - Sheka; Ariefandana , Muhammad Iqbal; Riansyah, Agus (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
KPPN Tanjungpinang has Filial services, Filial KPPN services are carrying out the tasks or activities of the KPPN front office which are placed in certain areas with certain criteria. With the condition of the Riau Islands Province which is in the form of islands, so that KPPN Tanjungpinang has the furthest or filial branch in Natuna Regency, with several outputs such as education in the context of preparing financial reports at the BUN level of authority; consultation on disbursement of funds; monitoring evaluation of competency development of KPA, PPK, PPSPM, Treasurer and Treasury Manager; and monitoring the evaluation of cash receipts and disbursements.